Mental health state of low vision patients using the hospital anxiety and depression scale and the depression, anxiety and stress scale - Mohd Harimi Abd Rahman,; Nadhrah AB,; Nur Hidayah Y,; Zainora Mohammed,; Jemaima Che Hamzah,; Mushawiahti Mustapha, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Mental health status of low vision (LV) patients is not a routine evaluation. This study was carried out to determine the mental health status among LV patient using Depression Anxiety Stress Scale (DASS-21) and Hospital Anxiety and Depression (HAD) Scale questionnaires. A total of 100 LV patients were recruited in this cross-sectional study. Standard LV assessment and mental health screening using DASS-21 and HAD Scale questionnaires were administered. The mean age of the subjects was 62.77+9.15 years old. There were 63% Malays, followed by 26% Chinese and 11% Indians. The mean visual acuity of the subjects was 0.45+0.24 LogMAR. Results showed the mean score for depression and anxiety for HAD scale questionnaire were 3.11+3.35 and 2.85+3.21, respectively. The mean score for depression, anxiety and stress for DASS questionnaire were 4.83+6.90, 3.58+3.79 and 6.18+6.92, respectively. The mean scores fell into the normal range classification of severity on both HAD scale and DASS. The HAD Scale showed that 12% of the subjects experienced depression and 8% experienced anxiety while the DASS showed that 7% had depression, 17% had anxiety and 24% experienced stress. These findings illustrate that the mental health of the LV patients can be affected due to visual impairment. In conclusion, the mental health status of LV patients can be screened objectively using DASS-21 and HAD Scale questionnaire. Understanding the mental health status of LV patients will enable us to provide better LV assessment and rehabilitation.